LITERATURE REVIEW : ANALYSIS OF THE IMPACT OF PRODUCTION EXPENDITURES, OPERATIONAL EXPENSES, PROMOTIONAL EXPENSES AND TOTAL SALES VOLUMES ON THE NET PROFIT IN PT AKASHA WIRA INTERNATIONAL Tbk PERIOD 2016-2017 - Anugerah Nurul Lucky; Muhammad Richo Rianto (Draf Solusi Indonesia, 2023)
This research aims to test whether production costs, operational costs, promotional costs and total salesvolume influencenot a professionalat PT Akasha Wira International Tbk for the 2016-2017 period. Thisresearch uses quantitative data samples and sampling uses purposive sampling techniques. The data analysis technique in this research uses multiple linear regression and classical assumption tests. Data processing in this research was assisted by the IBMSPSS 26 tool.